PEMIKIRAN SYEKH NAWAWI AL-BANTANI TENTANG PENDIDIKAN KARAKTER: ANALISIS KRITIS DALAM KONTEKS KURIKULUM MERDEKA - Fradana, Heru (Balai Diklat Keagamaan Jakarta, 2024)
Abstract This study aims to compare moral education according to Syekh Nawawi with character education in the strengthening project of the Pancasila Student Profile (P3) and the Rahmatan lil 'Alamin Student Profile (PPRA) in the Kurikulum Merdeka. The research question of this study is to identify the similarities and differences between these two approaches in terms of the roles of teachers, the roles of families, and the learning approaches. The research method used is library research, by reviewing various relevant literature sources, including the works of Syekh Nawawi, curriculum documents of Kurikulum Merdeka and related studies by various authors. The review procedure was conducted by collecting and analyzing data from books, articles, and journals that explain Syekh Nawawi's views on moral education, as well as the concepts and implementation of character education in Kurikulum Merdeka. The literature reviewed includes Syekh Nawawi's works such as “Marah Labib